DEVELOPMENT AND EVALUATION OF SOLID-LIPID NANO-PARTICLES OF SULFASALAZINE FOR ANTI- RHEUMATIC ACTIVITY (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Chronic rheumatoid arthritis (RA) can cause irreversible joint deterioration over time. Solvent-based lipid nanoparticles (SLNs) are widely used as an efficient method to increase the oral bioavailability of poorly soluble medicines like Sulfasalazine. The present study aimed to formulate and evaluation of anti-rheumatic potential of the solid lipid nano-particles (SLNs) of Sulfasalazine. Drug loaded SLNs were formulated and coated with chitosan (CS) for sustained delivery and characterized for particle size, poly dispersity index and in vitro drug release. safety and efficacy profile of optimized batch was analyzed in animal model. Particle size of the optimized formulation was 269±2.45 nm with the PDI of 0.217±0.008 and entrapment efficiency of about 79.9±2.21. The zeta potential of particles was 35.7 mV. Particles had spherical shape with size ranging 100 nm which was determined by TEM analysis. Created formulation showed that the medication was released from the lipid matrix under regulated conditions, with 83.2±1.5% of the drug released in 24 h. Cmax for drug was higher (337±24) when administered as SLNs drug, similarly Tmax was longer when administered as lipid nanoparticles (6Hr), indicating a sustained drug release from SLNs. complete Freund's adjuvant (CFA) activity in rats administered with CS-SSZ-SLN (300mg/kg) equivalent to doses of 300mg/kg SSZ showed reduction in paw edema by day 9 (53.1 ± 1.75% (p<0.005), day 18 (68.68 ± 2.08%) (p<0.001) and 78.24 ± 2.36 % ( p<0.001) on day 21 respectively. Significant increase in the Tmax and the T1/2 values for the nanoparticles, indicates sustained release of the drugs by the SLNs. Sulfasalazine functions by decreasing inflammation, which is likely responsible for lessening the signs and symptoms of inflammatory diseases such rheumatoid arthritis and inflammatory bowel disease.